Principle and Application Progress in Location-Based Services - Liu, Chun.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
These proceedings are aimed at researchers, industry / market operators and students from different backgrounds (scientific, engineering and humanistic) whose work is either focused on or affined to Location Based Services (LBS). It contributes to the following areas: positioning / indoor positioning, smart environments and spatial intelligence, spatiotemporal data acquisition, processing, and analysis, data mining and knowledge discovery, personalization and context-aware adaptation, LBS visualization techniques, novel user interfaces and interaction techniques, smartphone navigation and LBS techniques, three-dimensional visualization in the LBS context, augmented reality in an LBS context, innovative LBS systems and applications, wayfinding /navigation ( indoor/outdoor), indoor navigation databases, user studies and evaluations, privacy issues in LBS, usability issues in LBS, legal and business aspects of LBS, LBS and Web 2.0, open source solutions and standards, ubiquitous computing, smart cities, and seamless positioning.
Positioning and Indoor Positioning -- Spatiotemporal Data Acquisition, Processing, and Analysis -- Innovative LBS Systems and Application -- Smart Mobile Phone Navigation and LBS Techniques -- Data Mining and Knowledge Discovery.
Keywords: Geography; Data mining; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Electronic books